2021
DOI: 10.1111/1462-2920.15299
|View full text |Cite
|
Sign up to set email alerts
|

Root microbiome assembly of As‐hyperaccumulator Pteris vittata and its efficacy in arsenic requisition

Abstract: The assemblage of root-associated microorganisms plays important roles in improving their capability to adapt to environmental stress. Metal(loid) hyperaccumulators exhibit disparate adaptive capability compared to that of non-hyperaccumulators when faced with elevated contents of metal(loid)s. However, knowledge of the assemblage of root microbes of hyperaccumulators and their ecological roles in plant growth is still scarce. The present study used Pteris vittata as a model plant to study the microbial assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Das et al (2017) and Yu et al (2020) also demonstrated that soil arsenic pollution significantly reduced bacterial diversity in the P. vittata rhizosphere. Many studies concerning the effects of arsenic on microbial diversity in the rhizosphere of P. vittata have focused on culturable bacterial and fungal groups (Turpeinen et al, 2004;Das et al, 2016Das et al, , 2017Xiao et al, 2021). These studies have usually reported a reduced diversity of culturable bacteria and fungi due to arsenic pollution (Das et al, 2016), and they have also shown that arsenic pollution leads to an increase in the relative abundance of bacteria and fungi species/strains with tolerance and/or metabolic functions for arsenic (Turpeinen et al, 2004;Das et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Das et al (2017) and Yu et al (2020) also demonstrated that soil arsenic pollution significantly reduced bacterial diversity in the P. vittata rhizosphere. Many studies concerning the effects of arsenic on microbial diversity in the rhizosphere of P. vittata have focused on culturable bacterial and fungal groups (Turpeinen et al, 2004;Das et al, 2016Das et al, , 2017Xiao et al, 2021). These studies have usually reported a reduced diversity of culturable bacteria and fungi due to arsenic pollution (Das et al, 2016), and they have also shown that arsenic pollution leads to an increase in the relative abundance of bacteria and fungi species/strains with tolerance and/or metabolic functions for arsenic (Turpeinen et al, 2004;Das et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The perennial fern Pteris vittata (Chinese brake fern) was the first known arsenic hyperaccumulator to be highly tolerant and efficient in accumulating arsenic. Pteris vittata has been reported to accumulate up to 22,630 mg kg −1 dry weight of arsenic in fronds (Ma et al, 2001), arousing extensive research interest in its application in the phytoremediation of arseniccontaminated soil (Xie et al, 2009;Xiao et al, 2021). Studies have shown that the root exudates of P. vittata can affect soil pH, thereby altering the bioavailability of arsenic in soil (Yang et al, 2022), which is one of the main factors limiting the arsenic absorption efficiency of P. vittata.…”
Section: Introductionmentioning
confidence: 99%
“…The current results showed that the OTUs could be classified into two groups, those in the rhizosphere and those in the bulk soils, in both the AE and the NAE of S. alfredii ( Figure 2 ). Importantly, the rhizosphere soil-enriched OTUs were mainly identified as fast-growing bacteria that use various carbon sources, whereas the bulk soil-enriched OTUs were mainly identified as slow-growing bacteria that use only a few carbon sources ( Leff et al, 2015 ; Xiao et al, 2021a ). This result was agreed to prior work that plant roots recruit microorganisms from the associated bulk soils on the basis of their lifestyles ( Leff et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phytoextraction, the use of metal (hyper)accumulating plants to remove metal(loid)s from soils by concentrating them in the harvestable parts, has been proven as an eco-friendly and cost-effective alternative to remediate contaminated soils [33] and has received global attention due to its potential to restore soil quality and some functional capacities [34,35]. Moreover, a growing number of studies have shown that the association of hyperaccumulators with different microbial communities results in contrasting phytoremediation ability [36][37][38]. As a result, the metal hyperaccumulating plant has emerged as a model for disentangling the links between core microbiomes and plant functional characteristics, such as plant uptake and accumulation of heavy metals.…”
Section: Introductionmentioning
confidence: 99%